2012
DOI: 10.1007/s10896-012-9454-0
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Prevention and Health: Exploring Community Perceptions of Intimate Partner Violence in Rural Honduras

Abstract: This qualitative study rooted in community-based participatory research principles utilized semi-structured interviews with 2 focus groups (n=9) with female healthcare volunteers (FCVs) and 3 male key informants who were community leaders (MCLs). The study aimed to examine how a rural Honduran community defines and responds to intimate partner violence (IPV) in order to lay the foundation for future interventions. Based on grounded theory, the authors assessed for common themes across transcripts. Authors foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…However, an international study carried out in a rural setting revealed that the police and judiciary sectors still have great relevance in confronting violence in this scenario (24) . This view reinforces the idea that this problem belongs to these sectors, and perhaps there are no others available.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, an international study carried out in a rural setting revealed that the police and judiciary sectors still have great relevance in confronting violence in this scenario (24) . This view reinforces the idea that this problem belongs to these sectors, and perhaps there are no others available.…”
Section: Discussionmentioning
confidence: 99%
“…However, the priority actions of this sector occur in the urban context, and the rural populations are almost always deserted, although in many municipalities the rural population is larger (7) . Regarding the health sector, this has been pointed out by other studies as fundamental to the multi-and intersectoral response to violence against women, identifying and intervening from empathic listening, psychosocial support and referrals to other services (24)(25) . The education sector was also cited as an integral part of the coping network by study participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Do these findings point to the fact that IPV norms are primarily held at the fringe of the network, or are those at the fringe of the network more likely to admit finding IPV acceptable? Our results could be impacted by response bias-IPV is a sensitive topic and possibly underreported [ 46 ]. Under-reporting may differ depending on what potential social sanction an individual imagines as a result of supporting a stigmatized behavior- reporting itself may then be the consequence of a social norm.…”
Section: Discussionmentioning
confidence: 99%
“…Although, at the same time, one might wonder to what extent the home is a safe place for women to talk about their relationships with gangs and gang violence. Partner and domestic violence is often neglected and invisible, but at the same time widespread problem in Honduras (Sukhera et al 2012). Furthermore, requirements linked to the issue of confidentiality, like anonymity, would be impossible to guarantee, since I would have known where they lived (Yee and Andrews 2006).…”
Section: Ethics In Practice: Covert Practices In Overt Researchmentioning
confidence: 99%